Modeling Pengajaran dengan Teknik Total Phsical Response (TPR) Sebagai Variasi Pembelajaran Bahasa Inggris di SDN Gampingrowo 02 Sidoarjo - Edi Pujo Basuki; Novi Rahmania Aquariza; Tatik Muflihah; Destita Shari; Afib Rulyansyah (Utan Kayu Publishing, 2023)
English is very important and in the era of globalization English will be found in everyday life. Therefore, children must be provided with sufficient provisions as early as possible to get learning English, one of which starts from elementary school age because at that age between the ages of 6-13 years, children are in a critical period, namely experiencing very rapid development of the brain, so that easy to understand, remember and apply. SDN Gampingrowo 02 Sidoarjo, which is located in a remote area the of Tarik sub-district, is far from urban areas, making people have different thoughts about school. People in these areas tend to think that school is not important, so many children do not get an education. This results in a very small number of students in each class. The small number of students also makes teachers in the surrounding area less interested in working in the school which makes the school lack of teachers in it. Due to these conditions, we decided to do community service with the Total Physical Response (TPR) technique. TPR technique is a learning technique that focuses on body movement. This technique is often used in learning activities that require a student's memory. With movement, students are easier to memorize a vocabulary because they are not easily bored and move actively which can improve their ability to remember. This community service activity was carried out on Wednesday and Thursday, 22-23 June 2022. This activity lasted for 2 consecutive days. The results of this community service activity show that by teaching modeling with the Total Physical Response (TPR) technique 5th-grade students at SDN Gampingrowo 02 Sidoarjo, totaling 10 people, can understand English vocabulary easily. The TPR technique is very influential and succession introducing basic English to elementary school students. In addition, teachers can find out about learning with TPR strategies, namely using body movements and music. The TPR strategy can also train students' self-confidence. So, it is highly recommended to use the Total Physical Response (TPR) technique when adding English vocabulary.